Equity and gender mainstreaming in public policy: A scoping review protocol. - Michelle Amri; Jinny Yang; Geneviève Jessiman-Perreault; Amne Haikal; Kathryn Barrett; Jesse B Bump (PLoS ONE)
Background Despite growing attention paid to health equity and efforts to promote gender mainstreaming-a global strategy to promote gender equality-how policymakers have 'institutionalized' this in their work is less clear. Therefore, this planned scoping review seeks to search the peer-reviewed and grey literature to compile evidence on the ways in which policymakers have routinely or systematically considered equity and/or gender in their work. Methods A scoping review will be undertaken by drawing on the PRISMA guidelines for Scoping Reviews (PRISMA-ScR). With the expert guidance of a research librarian, Ovid MEDLINE, Ovid EMBASE, PAIS Index, and Scopus databases will be searched, in addition to custom Google searches of government documents. The search will be conducted from 1995 and onwards, as there were no hits prior to this date that included the term "gender mainstream*" in these databases. The inclusion criterion is that: (i) texts must provide information on how equity and/or gender has been considered by government officials in the development of public policy in a routine or systematic manner (e.g., descriptive, empirical); (ii) both texts produced by government or not (e.g., commentary about government action) will be included; (iii) there are no restrictions on study design or article type (i.e., commentaries, reports, and other documents, would all be included); and (iv) texts must be published in English due to resource constraints. However, texts that discuss the work of nongovernmental or intergovernmental organizations will be excluded. Data will be charted by: bibliographic information, including the authors, year, and article title; country the text discussed; and a brief summary on the approach taken. Discussion This protocol was developed to improve rigour in the study design and to promote transparency by sharing our methods with the broader research community. This protocol will support a scoping review of the ways in which policymakers have routinely or systematically considered equity and/or gender in their work. We will generate findings to inform government efforts to initiate, sustain, and improve gender and equity mainstreaming approaches in policymaking.